A qualitative study of patients’ and caregivers’ perspectives on educating healthcare providers - Holly Adam (Canadian Medical Education Journal, 2021)
Background: Patients/caregivers can be actively involved in the education of healthcare providers (HCPs). The purpose of this study was to explore patients'/caregivers' perspectives on their involvement and roles in the education of HCPs.